PENGARUH LATIHAN FISIK AEROBIK TERHADAP KAPASITAS FUNGSIONAL PASIEN GAGAL JANTUNG KRONIK PADA USIA LANJUT - , Mochammad Khalimur Rouf ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chronic heart failure is a frequent disease to arise and cause death in admission patients especially the elderly. Almost half of old patients with chronic heart failure experience repeated care in the hospital since after 6 months of first admission. In elderly, multidisciplinary approaches are essential because of the complexicity of the disease, polipharmacy, comorbidity, and quality of life which can improve overall morbidity and mortality. The main focus of cardiac rehabilitation recently is exercise designed for stable heart failure patients and is used as one of the modality of therapy. Beside the efffort to improve the disease and to use set of helping tool, exercise is recommended as one of modality in managing heart failure to improve prognosis, increase pysical activity tolerance and overall quality of life of heart failure patients. The objective of this study is to understand is aerobic exercise programme can improve functional capacity in geriatric heart failure patients. The design of this study is randomized controlled trial. The subject of the study were men and women with chronic heart failure functional class I-II of NYHA aged > 60 years and are submitted and agreed to be included to the study. Sample were divided into two group randomly, which were the exercise group and the control group. To compare the functional capacity of both groups, t-test independent is used with condition of normal data range and Mann Whitney test is used if abnormal data range is found.